PATRON STRATEGY IN MAINTAINING COOPERATION RELATIONSHIPS WITH FISHERMEN IN LUBUK TUKKO BARU OF PANDANSUB-DISTRICTOF TAPANULI TENGAH REGENCY OF NORTH SUMATRA PROVINCE - Ade Cai Serini Marbun; Kusai Kusai; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in February 2018, located in Lubuk Tukko Baruof Pandan Sub-district of Tapanuli Tengah Regency of North Sumatera Province. The study was aimed to: 1) Know the factors that resulted in the fishermen willing to cooperate with patron; 2) Analyzing the pattern of fishing relationships with Tauke in Lubuk Tukko Baru and 3) Analyze the strategy for social and economic progress in maintaining cooperation with fishermen. The method used in this research is a qualitative phenomenological method with the determination of informants in simple random sampling. Based on the results of research obtained, that the factors that led to the fishermen want to cooperate with patron, that’s due to a relationship of interdependence between patron with fishermen, patron aid to fishermen and fishermen assistance to tauke. While the relationship pattern of fishermen and Tauke cooperation there are three that have elements, That are: the element of working relationships that occur because of the activities of fishermen and patron, elements of economic relations that occur through economic activity and social relations elements occur social interaction in economic relations. To maintain such cooperation relationship, patron has social and economic strategy. Social strategy patron the aid of consumption, aid fishing equipment, easy loan process, kinship relationships that exist between patron with fishermen. While patron economic strategy is the pattern of rent / profit sharing, opening a patron business and patron credit management.Keywords: Patron,Strategy,Client,Relationship, Fisherman